Multiple mating affects queen productivity on neotropical ants, a study on Odontomachus chelifer - Florindo, Henrique Silva (Universidade Estadual Paulista (Unesp), 2023)
The features that influence one’s ability to reproduce are diverse. In ants, aside from environmental conditions and genetic attributes, reproductive strategies also influence an organism’s Reproductive Output (RO). We aimed to investigate the contribution of environmental, colony structure, and genetic factors to the RO of queens of Odontomachus chelifer, a polygynous species distributed throughout the Cerrado, the Brazilian savanna. We tested four hypotheses separately using generalized linear models: 1. RO decreases with higher polygyny levels; 2. RO increases with higher polyandry levels; 3. RO increases with higher heterozygosity; 4. RO increases with more food resources available. Also, we used Structural Equation Modeling (SEM), evaluating multifactorial relationships between variables. We analyzed 15 workers from 18 colonies (n = 270 workers), reconstructing the parental lineages of the colonies. We sampled arthropods along the study area, estimating the mean abundance and Shannon’s Diversity Index of each sampling site. We inferred the number of queens per nest, the number of male mates per queen, and the proportion of offspring generated per queen, the latter being used as a proxy for RO. Our results indicated that polyandry explains most of queens RO, presenting a positive effect on the proportion of offspring generated, the remaining variables presented non-significant effects.

As características que influenciam a habilidade de reprodução de um organismo são diversas. Em formigas, além de condições ambientais e fatores genéticos, estratégias reprodutivas também podem influenciar seu desempenho reprodutivo (DR). Nós visamos investigar a contribuição de fatores ambientais, genéticos e de estrutura de colônia ao DR de rainhas de Odontomachus chelifer, uma espécies poligínica de distribuída pelo Cerrado. Nós testamos quatro hipóteses separadamente utilizando modelos lineares generalizados (GLMs): 1. DR reduz com maiores níveis de poliginia; 2. DR aumenta com maiores níveis de polandria; 3. DR aumenta com maior heterozigosidade; 4. DR aumenta com maior disponibilidade de recursos alimentares no ambiente. Adicionalmente, utilizamos Modelagem por Equações Estruturais (SEM), para avaliar relações multifatoriais entre as variáveis. Nós analisamos 18 colônias, amostrando 15 operárias de cada uma (n = 270 operárias), reconstruindo as linhagens parentais das colônias. Nós amostramos artrópodes ao longo da área de estudo, estimando a abundância média e o Índice de Diversidade de Shannon de cada área de amostragem. Nós inferimos o número de rainhas por ninho, o número de cópulas com machos por rainha, a proporção de prole gerada por rainha, este último utilizado como proxy para DR. Nossos resultados indicaram que a poliandria explica a maior parte da variação no DR de rainhas, apresentando um efeito positivo na proporção de prole gerada, o restante das variáveis apresentaram efeitos não-significativos.
Múltiplas cópulas afetam desempenho reprodutivo de formigas neotropicais: um estudo em Odontomachus chelifer (Hymenoptera: Formicidae)
Keywords: Evolução; Poliandria; Insetos Sociais